(untitled) (Bioagro, 2024)
Rice is one of the most important agricultural crops in Venezuela and knowledge of the seed vigor can provide information about its eventual performance in the field. Seeds of eight rice cultivars with different storage times were subjected to standard germination (PG), field emergence (EC), first germination count (Pc5) and accelerated aging (EA) tests, in order to evaluate the last two methods as indicators of seed vigor. PG results varied among rice cultivars, and for all of them, EC was always lower than PG, confirming the greater stress under field conditions. There was no correlation between storage time and PG or EC, evidencing other factors affecting seed germination. The regression line of EC as a function of PG was moderate and explained less than 50 % of data variability. Pc5 showed a low association with the field emergence (r2 = 0.1753), and among the evaluated EA methods, incubation for 72 hours (EA72) showed the best association with field emergence (r2 = 0.6669; P = 0.0134), thus being the most indicated method here for the estimation of rice seed vigor of the tested cultivars under the trial environment.